Improving the Living Standards of the Population through the Development of Family Entrepreneurship and Small Business in Uzbekistan - G. T. Samiyeva; B. I. Khaydarov (International Journal on Economics, Finance and Sustainable Development, 2022)
The article discusses the role and importance of family business and entrepreneurship in poverty reduction, highlights the theoretical foundations of family business.